Perceived Ethical Climate and Unethical Behavior: The Moderating Role of Moral Identity - McCorvey, Kellie; Woehr, David J. (Journal of Leadership, Accountability and Ethics, 2022)
Unethical behavior in organizations results in significant negative outcomes, including financial impacts such as decreased shareholder value and profitability as well as non-financial impacts such as poor employee morale and reputation. This research empirically examines the moderating role of moral identity on the relation between ethical climate perceptions and unethical behavior as reflected by moral disengagement, unethical pro-organizational behavior, and ethical judgment. Moral identity was hypothesized to moderate the impact of ethical climate on unethical behavior such that higher levels of moral identity reduced the propensity to engage in unethical behavior in all ethical climate types. Moral identity internalization, but not moral identity symbolization, was found to have significant correlations with unethical behavior as well as the predicted moderating effects on the relationships between ethical climates and unethical behavior. Theoretical and practical implications and future research directions are discussed.